STRUKTUR KOMUNITAS DIATOM EPILITIK PERAIRAN SUNGAI SENAPELAN DAN SUNGAI SAIL, KOTA PEKANBARU. - Rizka Aprisanti; Aras Mulyadi; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2013)
The aims of this research to assess the environmental condition of the Senapelan river and Sail river waters by the species abundance of epilithic diatom. This research identified 14 genera of epilithic diatom. The abundance of epilithic diatom at Senapelan river 48.779cell/cm2 and Sail river 15.564 cell/cm2. The value of diversity indices (H '), Senapelan river(2.936) and Sail river (2.336), the value of equability indices (E '), Senapelan river (0.691)and Sail river (0.550), and the dominant indices (C'), Senapelan river (0.187) and the Sailriver (0.336). Based on these indices Senapelan river and Sail river were included intomoderate polluted waters. Species that dominate Senapelan river and Sail river waters ofPekanbaru City are Navicula sp., Nitzchia sp, Fragilaria sp. and Melosira sp.